Mass spectrometry-based proteomics to delineate the complete histone code in both asexual and gametocyte stages of Plasmodium falciparum - Birkholtz, Lyn-Marie (2026)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2014.